Pengaruh Obedience Pressure, Kompleksitas Tugas dan Independensi terhadap Kualitas Audit - Sedjati, Retina Sri; Amalia, Liska Indah (DFAME Digital Financial Accounting Management Economics Journal, 2023)
This paper investigates the intricate relationships between obedience pressure, task complexity, independence, and audit quality, drawing insights from selected studies. The research underscores the vital role of independence in mitigating external pressures, highlights the amplified impact of obedience pressure under high task complexity, and emphasizes the need for tailored training to navigate challenges. Theoretical frameworks shed light on auditor behavior, accentuating the importance of resilience and ethical conduct. Comparative analysis reveals the nuanced interplay of factors influencing audit quality, offering a holistic perspective for auditors, regulators, and stakeholders seeking to enhance trust, transparency, and accountability in the audit process